Role of Ferroptosis in Lung Diseases - Xu W; Deng H; Hu S; Zhang Y; Zheng L; Liu M; Chen Y; Wei J; Yang H; Lv X (Dove Medical Press, 2021)
Wenting Xu,1,2,* Huimin Deng,2,* Song Hu,2,3,* Yiguo Zhang,2,3 Li Zheng,1,2 Meiyun Liu,2 Yuanli Chen,2 Juan Wei,2 Hao Yang,2 Xin Lv1– 3 1Department of Anesthesiology, Fuyang Hospital of Anhui Medical University, Fuyang, Anhui, 236000, People’s Republic of China; 2Department of Anesthesiology, Shanghai Pulmonary Hospital, Tongji University School of Medicine, Shanghai, 200433, People’s Republic of China; 3Graduate School, Wannan Medical College, Wuhu, AnHui, 241002, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Lv; Hao YangDepartment of Anesthesiology, Shanghai Pulmonary Hospital, Tongji University School of Medicine, 507 Zhengmin Road, Shanghai, 200433, People’s Republic of ChinaEmail xinlvg@126.com; yanghaozunyi@sina.comAbstract: Ferroptosis is a new type of programmed cell death characterized by intracellular iron accumulation and lipid peroxidation that leads to oxidative stress and cell death. The metabolism of iron, lipids, and amino acids and multiple signalling pathways precisely regulate the process of ferroptosis. Emerging evidence has demonstrated that ferroptosis participates in the occurrence and progression of various pathological conditions and diseases, such as infections, neurodegeneration, tissue ischaemia-reperfusion injury and immune diseases. Recent studies have also indicated that ferroptosis plays a critical role in the pathogenesis of acute lung injury, chronic obstructive pulmonary disease, pulmonary fibrosis, pulmonary infection and asthma. Herein, we summarize the latest knowledge on the regulatory mechanism of ferroptosis and its association with iron, lipid and amino acid metabolism as well as several signalling pathways. Furthermore, we review the contribution of ferroptosis to the pathogenesis of lung diseases and discuss ferroptosis as a novel therapeutic target for various lung diseases.Keywords: ferroptosis, metabolic networks and pathways, signalling pathways, lung diseases